A Bibliometric Analysis of Acupuncture Treatment of Postoperative Complications from 2003 to 2023 - Zhu D; Xu W; Ye W; Jiang Y; Jiao L; Chen R (Journal of Multidisciplinary Healthcare, 2025)
Daocheng Zhu,1,2,* Wei Xu,1,2,* Wenguo Ye,1,2 Yuexia Jiang,1,2 Lin Jiao,1,2 Rixin Chen1,2 1Jiangxi University of Chinese Medicine, Nanchang City, Jiangxi Province, People’s Republic of China; 2The Affiliated Hospital of Jiangxi university of Chinese Medicine, Nanchang City, Jiangxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Jiao, Jiangxi university of Chinese Medicine, Nanchang City, Jiangxi Province, People’s Republic of China, Email jl0809@126.com Rixin Chen, Jiangxi university of Chinese Medicine, Nanchang City, Jiangxi Province, People’s Republic of China, Email chenrixin321@163.comBackground: Postoperative complications refer to some related clinical symptoms that occur after surgery, which can affect7 the patient’s recovery. Acupuncture has a good effects on postoperative complications, which can accelerate postoperative recovery. Currently, there are many literature studies in this field. However, there has been no quantitative analysis of these literature. Therefore, in this study, the bibliometric method was adopted to analyze the relevant literature, thereby exploring the research hotspots and trends in this field.Methods: Through the web of science core database, we collected the relevant literature on the acupuncture treatment of postoperative complications from 2003 to 2023, used citespace software to analyze the author, publishing institution, country, keywords, references, cited journals and other information of these literature, and analyzed its research hotspots and research trends through a visual view.Results: A total of 213 articles were obtained, and the annual publication volume overall is on the rise, especially in recent years when the publication volume has surged. The field with the highest number of publications is Integrative Complementary Medicine. The most cited journal is Evidence-Based Complementary and Alternative Medicine. The country with the highest number of publications is China, and the institution with the highest number of publications is Capital Medical University. The author with the highest number of publications is Zhu, Junchao. The most central cited author is LEE A. The articles with the highest frequency and centrality of cited references are published by Liu, Y. H. The most frequently studied keywords are acupuncture.Conclusion: This study systematically analyzes the current research status and hotspots of acupuncture treatment for postoperative complications in the past 20 years, which can help researchers grasp the current research direction and provide reference basis for further research.Keywords: acupuncture, postoperative complications, bibliometric analysis, research trends